2018
DOI: 10.21037/apm.2018.05.14
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening palliative care delivery in developing countries: a training workshop model in Botswana

Abstract: Here we provide quantitative data that supports the success of the training workshop model presented. Improvement in palliative care knowledge and treatment skills, as evidenced by the increased scores from pre- to post-test results, suggests the efficacy of this 2-day training program in advancing palliative care education of nurses. Given the unmet need for healthcare workers trained in palliative care, this model could serve as a valuable tool for expanding and strengthening the delivery of care in settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…To date, only a handful of doctors and nurses have attended short courses in palliative care [42]. Contextually appropriate palliative care education through nursing and medical education, and as 'in-service' training programs for healthcare professionals are essential [8,[43][44][45]. Evidence indicates that education and training has improved knowledge and skills [46], changed attitude towards the care of very ill and dying patients [47] and enhanced access to opioid analgesics [32].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a handful of doctors and nurses have attended short courses in palliative care [42]. Contextually appropriate palliative care education through nursing and medical education, and as 'in-service' training programs for healthcare professionals are essential [8,[43][44][45]. Evidence indicates that education and training has improved knowledge and skills [46], changed attitude towards the care of very ill and dying patients [47] and enhanced access to opioid analgesics [32].…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] PC education should be available through undergraduate medical and nursing education and as part of in-service training for health professionals, social workers and spiritual caregivers involved with patients with life-limiting illnesses. [ 65 ] Specialist PC training should also be available for professionals at the community level so that quality services enable patients to stay at home. [ 53 ] Media and public advocacy and family caregiver training are important avenues to create awareness, increase knowledge and change attitudes among policy makers, drug regulators, traditional healers, patients and families.…”
Section: Discussionmentioning
confidence: 99%
“…[12] For public health strategies to be effective, PC should be implemented at all levels of healthcare and community. [12,65] This review found that PC services in most LICs were available variably in hospitals, hospices, cancer and HIV/AIDS centres, faith-based institutions and communities including mobile services such as road side clinics and as homebased care. However, in some LICs, PC is available only in urban areas [24,25] or not available at all.…”
Section: Sociocultural and Spiritual Componentsmentioning
confidence: 99%
“…Importantly, a key component for advancing global palliative care is the training of nurses. Although several pilot projects in LMICs have successfully integrated nurses into community-based palliative care teams, an important gap is the lack of inclusion of geriatric principles, which is also a significant priority in geriatric oncology [114,119,120].…”
Section: Resource-constrained Settingsmentioning
confidence: 99%